Synthesis and Biological Evaluation of Some Tri- and Tetra-Substituted Pyrazoles and Isoxazoles - Solanki, P.R.; Wadodkar, K.N.; Rai, M.K.; Wagh, Preeti (Asian Journal of Chemistry, 2010)
A series of tri and tetra-substituted pyrazoles and isoxazoles were synthesized by the reaction between 3-acetylflavone (IIa-f) and hydrazine hydrate, phenylhydrazine and hydroxylamine hydrochloride respectively.The new compounds were screened for their antibacterial activity.